Pengaruh tata kelola syariah terhadap efektivitas manajemen risiko di lembaga keuangan syariah - -, Farah Salsabila (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the impact of Sharia governance on the effectiveness of risk management in Islamic Financial Institutions (IFIs), focusing on the role of governance mechanisms such as the Sharia Supervisory Board (SSB) and Internal Sharia Review (ISR). Islamic financial institutions face various risks, including financing risk, operational risk, and reputational risk, which can affect the institutions' stability and sustainability. This research finds that sound Sharia governance can significantly mitigate risks by ensuring that products and services comply with Sharia principles, strengthening internal oversight, and maintaining compliance with Sharia regulations. A competent SSB plays a key role in reducing operational and legal risks, while ISR helps minimize credit risk and ensures that financial transactions comply with Sharia standards. The study also highlights the importance of transparency and accountability in risk management within IFIs. By implementing strong Sharia governance, Islamic financial institutions can maintain financial stability and enhance their long-term institutional performance. Overall, this study provides insights into the contribution of Sharia governance in managing risks and strengthening the sustainability of Islamic financial institutions.